Effects of adding Sophora alopecuroides to high concentrate diet on rumen fermentation parameters and microbial diversity of sheep - An, Yawen; Wang, Hairong; Zong, Zichao; Gao, Zhixiong; Shi, Caixia; Li, Shufang; Khas-Erdene, (Frontiers in Veterinary Science, 2023)
The purpose of this experiment was to study the effects of different doses of Sophora alopecuroides (SA) on rumen fermentation and microbial diversity in sheep. A total of 20 healthy Dumont crossbred male lambs weighing 25.73 ± 2.17 kg were randomly divided into four groups with five replicates each. The control (CG) group was fed basal diet with a 7 : 3 concentrate-to-forage ratio, while group 1 (TG1), group 2 (TG2) and group 3 (TG3) were fed with 0.1%, 0.3% and 0.5% SA, respectively. The results were as follows: (1) Compared with the control group, the addition of SA to high concentrate diet significantly increased the concentrations of acetic acid, propionic acid, TVFA and the ratio of ethylene to propylene in the rumen of the experimental group (P < 0.05) , significantly decreased the concentration of rumen ammonia nitrogen (P < 0.05) , and significantly increased the rumen pH of the TG3 group (P < 0.05). (2) At the level of rumen bacterial phyla, the abundance of Bacteroidetes in the diet increased and that of Firmicutes decreased (P = 0.08); At the genus level, the abundance of Ruminococcus and Phocaeicola in the rumen of the three experimental groups were significantly higher than that of the control group (P < 0.05), and the abundance of Clostridiales and Candidatus-Hepatincola were significantly increased in the TG1 and TG2 groups (P < 0.05). (3) For rumen anaerobic fungi, the differences between control and test groups were not significant (P > 0.05) at the phylum level and genus level, but the relative abundance of Neocallimastigomycota and Piromyces in the TG1 group was significantly higher than that in the control group. In conclusion, the addition of SA to the diet could promote rumen fermentation, reduce rumen pH, maintain the homeostasis of the rumen environment in sheep, fine-tun the composition of the rumen microbiota and volatile fatty acids. It had an important impact on the improvement of body health under the condition of high concentrate diet.